TEACHING AND METHODS OF ATOMIC AND NUCLEAR PHYSICS IN CONTINUING EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today, the improvement and further development of the education system is a global demand. In the world, the problem of developing independent thinking skills of Lifelong learning professionals is relevant in the field of education. In the context of globalization in accordance with the UNESCO Convention on Technical and Vocational Education, it is important to develop students creative thinking and creative abilities through the creation and implementation of innovative technologies of educational services based on labor market requirements.